Sosialisasi Sistem Monitoring Cleaning Service dan Edukasi Karyawan PT. Fiyansa di Dusun Kampung Baro Sidoarjo [Socialization of Cleaning Service Monitoring System and Employee Education at PT. Fiyansa in Dusun Kampung Baro Sidoarjo] - Budiarti, Rizqi Putri Nourma; Lailiyah, Nilna Muna; Mujiyanto, Rachmat; Amalia, Nadia; Anam, Muhammad Wildan Khoirul; Sahri, Moch (UKInstitute, 2025)
Abstract. Cleanliness and health of the work environment play a crucial role in supporting productivity, comfort, and organizational image. Common challenges include limited monitoring of cleaning staff performance and low employee awareness in maintaining cleanliness. This community service program aims to improve the quality of cleanliness and health in office environments through the socialization of technology-based performance monitoring systems and education on cleanliness behavior for employees. The activities were carried out in Dusun Kampung Baro, Buncitan Village, Sedati District, Sidoarjo Regency using both face-to-face and online methods to reach a wider range of participants. The materials covered the introduction of monitoring technology, training on the use of direct reporting features, and learning clean behavior through discussions, case studies, and simulations. The results showed an increase in participants’ understanding of the monitoring system, the growth of collective awareness in maintaining cleanliness, and motivation to consistently apply clean behavior. The combined training method proved effective in maintaining the quality of interaction and delivery of materials, while also expanding the program's reach. This activity has the potential to become a model for cleanliness management that integrates technology and behavioral development, and can be adapted to various other work environments. Abstrak. Kebersihan dan kesehatan lingkungan kerja berperan penting dalam mendukung produktivitas, kenyamanan, dan citra organisasi. Tantangan yang sering muncul adalah keterbatasan pemantauan kinerja petugas kebersihan dan rendahnya kesadaran karyawan dalam menjaga kebersihan. Program pengabdian masyarakat ini bertujuan meningkatkan kualitas kebersihan dan kesehatan lingkungan perkantoran melalui sosialisasi sistem pemantauan kinerja berbasis teknologi serta edukasi perilaku kebersihan kepada karyawan. Kegiatan dilaksanakan di Dusun Kampung Baro, Desa Buncitan, Kecamatan Sedati, Kabupaten Sidoarjo dengan metode tatap muka dan daring untuk menjangkau peserta lebih luas. Materi meliputi pengenalan teknologi pemantauan, pelatihan penggunaan fitur pelaporan secara langsung, dan pembelajaran perilaku bersih melalui diskusi, studi kasus, dan simulasi. Hasil kegiatan menunjukkan peningkatan pemahaman peserta terhadap penggunaan sistem pemantauan, tumbuhnya kesadaran kolektif menjaga kebersihan, serta motivasi menerapkan perilaku bersih secara konsisten. Metode pelatihan gabungan terbukti efektif menjaga kualitas interaksi dan penyampaian materi, sekaligus memperluas jangkauan program. Kegiatan ini berpotensi menjadi model pengelolaan kebersihan yang mengintegrasikan teknologi dan pembinaan perilaku, sehingga dapat diadaptasi di berbagai lingkungan kerja lainnya.